(untitled) (The South East European Journal of Economics and Business, 2022)
This study analyses the role of investment in intangible and tangible fixed assets on firm internationalisation pace. Financial microdata of the largest 300 Croatian exporters for the period 2006-2015 were examined by system dynamic panel GMM. Results illustrate that investments in intangible assets significantly and positively increase export growth but not domestic revenue growth. The study also analysed differences in internationalisation and localisation growth depending on investments in intangible and tangible fixed assets. Investments in intangible assets positively affect firm internationalisation growth, while an increase in intangible assets negatively affects localisation growth. Significance of this study is twofold. Firstly, it provides evidence of the importance of investments in intangible assets for export growth and internationalisation growth. Secondly, it shows that investments in intangible assets are more important that investments in fixed assets, thereby providing practical implication for firms aiming to increase the pace of their international expansion.